2006
DOI: 10.1083/jcb.200602046
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase–like proteins play opposing roles during retrotranslocation

Abstract: Misfolded proteins in the endoplasmic reticulum (ER) are retained in the organelle or retrotranslocated to the cytosol for proteasomal degradation. ER chaperones that guide these opposing processes are largely unknown. We developed a semipermeabilized cell system to study the retrotranslocation of cholera toxin (CT), a toxic agent that crosses the ER membrane to reach the cytosol during intoxication. We found that protein disulfide isomerase (PDI) facilitates CT retrotranslocation, whereas ERp72, a PDI-like pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(147 citation statements)
references
References 20 publications
7
139
0
1
Order By: Relevance
“…S4). These results demonstrate that the PDIinduced shift of CTA1 to a protease-sensitive conformation, which has been interpreted as an unfolding event (9,13,23,28,29), does not correlate to the PDI-induced separation of CTA1 from CTA2/CTB 5 .…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…S4). These results demonstrate that the PDIinduced shift of CTA1 to a protease-sensitive conformation, which has been interpreted as an unfolding event (9,13,23,28,29), does not correlate to the PDI-induced separation of CTA1 from CTA2/CTB 5 .…”
Section: Discussionmentioning
confidence: 71%
“…The unfoldase activity of PDI in this process is, to the best of our knowledge, a unique property that has not been reported for PDI interactions with any other substrate. Furthermore, the proposed unfoldase activity of PDI is based upon a protease sensitivity assay that only serves as an indirect measure of protein folding (9,13,23,28,29). In this work, we demonstrated that PDI is required for disassembly of the CT holotoxin but does not unfold the CTA1 subunit.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The same set of factors participating in protein folding and assembly, such as immunoglobulin binding protein (BiP), calnexin, and the family of protein disulfide isomerases, is involved in recognition and retention of folding-defective products [50][51][52].…”
Section: Eradmentioning
confidence: 99%